Determinants of the Socio-economic status of the Sea Food Harvesting Communityof Peninsular, Jaffna - Umashankar, K.; Shalton, A.R. (Sri Lanka Agricultural Economics Association, 2018)
Considering the Northern coastal belt of the Island, it could be seen that the Peninsular coastline is quite adapt in sustained sea food harvesting for a substantial length of time. A community which endured hardship, and destruction, are contending another aggression. Unpredictable weather pattern along with poaching, use of illegal methods and indiscriminate harvesting render their time, energy and money spent in vain. As a result, these people have been confined to poverty and privation. This research attempts to find the socio economic factors which have contributed to the conditions of life of these people. A total of 176 fishing households were selected using purposive random sampling method, during the period of February to April, 2017. The poverty level of the respondents was assessed based on the Multidimensional Poverty Index in compliance with UNDP HDRO standards. Using the Binary Response Logistic Model, an effort was made to decipher what community base factors are responsible for their state of poverty. It was found that membership in fishermen organization (-0.3264) and income generated from fishing activity (-0.1521). income diversification practices of households (-0.0473) and the educational level of the household head (-0.0041) influence poverty negatively at 1 percent, 5 percent, 5 percent and 1 percent significant levels respectively, whereas, utilizing child labour (0.0586) contributed positively towards poverty at 1% significant level. Encouraging households to enrol as members of local fishing communities helps the member households emerge from poverty. Further, the membership entitles the relevant households for institutional credit, marketing facilities, contract opportunities and cold storage facilities etc. Enhanced bargaining power is also found through the communities. Besides, income earned through plain fishing alone, income diversification helps to reduce poverty. To this end, a reasonable amount of training is required in a variety of endeavours. Child labour could not be encouraged in that, shaping of the personality of the child, suffers due to lack of training in the relevant field and lack of a short spell of formal education. A time of training in the sphere of fishing will give the required skill that will equip the adult fisherman which will help reduce poverty.
Keywords: Fishing household; Jaffna peninsula; Logistic model; Poverty; Social parameters